Top-down, Bottom-up and Sideways: The Multilayered Complexities of Multi-level Actors Shaping Forest Governance and REDD+ Arrangements in Madre de Dios, Peru - Rodríguez Ward, D.; Larson, A.M.; Gordillo-Ruesta, H.A. (Springer, 2018)
This study examines the role multilevel governance plays in the adoption of sustainable landscape management initiatives in emerging arrangements aimed at reducing emissions from deforestation and forest degradation (REDD+). It sheds light on the challenges these multiple layers of actors and interests encounter around such alternatives in a subnational jurisdiction. Through transcript analysis of 93 interviews with institutional actors in the region of Madre de Dios, Peru, particularly with regard to five sites of land-use change, we identified the multiple actors who are included and excluded in the decision-making process and uncovered their complex interactions in forest and landscape governance and REDD+ arrangements. Madre de Dios is a useful case for studying complex land-use dynamics, as it is home to multiple natural resources, a large mix of actors and interests, and a regional government that has recently experienced the reverberations of decentralization. Findings indicate that multiple actors shaped REDD+ to some extent, but REDD+ and its advocates were unable to shape land-use dynamics or landscape governance, at least in the short term. In the absence of strong and effective regional regulation for sustainable land use alternatives and the high value of gold on the international market, illegal gold mining proved to be a more profitable land-use choice. Although REDD+ created a new space for multilevel actor interaction and communication and new alliances to emerge, the study questions the prevailing REDD+ discourse suggesting that better coordination and cooperation will lead to integrated landscape solutions. For REDD+ to be able to play a role in integrated landscape governance, greater attention needs to be paid to grassroots actors, power and authority over territory and underlying interests and incentives for land-use change.